A mão-de-obra como barreira ao desenvolvimento empresarial - Pinheiro, Ana Paula Gonçalves Varca (2004)
Recent changes in the world have produced a peculiar demand for laborers' capacity due to the fiercer competition caused by the opening of the markets; to the irreversible process of Globalization; and, especially, to the growing use of new technologies, which have become more and more widespread in contemporary society. Therefore, new patlems of qualification were established. The worry about the necessity of forming able workers to face the challenges, which this new juncture imposes, is shared by govemments of several nations, which endeavor to reformulate the basic guidelines on education aiming, besides the job market, sustainable development. This paper investigated one of the obstacles to the progress of micro and small companies and their influence on organizational development: qualification of labor force. This multifarious theme involves various parts: govemments, companies and, also, the worker himself with his educational problems in a world in ongoing change. This paper refers to govemmental actions and other more general aspects; nevertheless, it emphasizes the difficulty of the manager, and his perspective; who, in an atlempt to fulfill the demands of his job, cannot find qualified laborers available. The theoretical reference used was by authors who adopted postfordism and postmodemism paradigms, combined with bibliographic research, to conceptualize the abilities, which are required by companies, and the govemmental actions that aim employment. Moreover, managers of labor force and of micro and small companies, which install infrastructure for the electrical and telecommunications sectors in the Middle West, Southeast and South of Brazil, were interviewed. The research concluded that, in the sector studied, there is no unemployment or excess of labor force; but lack of preparedness, lack of qualified labor force to the occupations, which have remaining vacancies. Lack of preparedness is detected in basic skills such as reading and writing, what blocks not only the specialization of the worker, his improvement, but also the sustainable development of small and micro companies in Brazil. The results of this research indicate that basic qualification of labor force is an obstacle to development, which is an issue that goes beyond the scope of business organization.